2022
DOI: 10.1007/s12652-022-03901-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolving deep convolutional neural networks by IP-based marine predator algorithm for COVID-19 diagnosis using chest CT scans

Abstract: This paper proposes an optimal structured deep convolutional neural network (DCNN) based on the marine predator algorithm (MPA) to construct a novel automatic diagnosis platform that may help radiologists identify COVID-19 and non-COVID-19 patients based on CT scan categorization and analysis. The goal is met with the help of three modifications based on the regular MPA. First, a novel encoding scheme based on Internet Protocol (IP) addresses is proposed, followed by introducing an Enfeebled layer to build a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Liu et al [230] introduced a new framework named DCNN + IMPA (internet protocol marine predator) to diagnose COVID-19. They reported that the model achieved an accuracy of 97.57%.…”
mentioning
confidence: 99%
“…Liu et al [230] introduced a new framework named DCNN + IMPA (internet protocol marine predator) to diagnose COVID-19. They reported that the model achieved an accuracy of 97.57%.…”
mentioning
confidence: 99%